Renewable energy choice: Cost and energy analysis of grid connected photovoltaic system in Malaysia - Heng, L.C.; Al-Amin, A.Q.; Saidur, R.; Ward, T.A. (Wiley Black, 2015)
Conventional energy production methods rely upon combustion of hydrocarbon fuels, which exhaust gases that can elevate the temperature of the Earth's atmosphere (greenhouse effect). Alternative methods of power generation are being examined that do not have this negative environmental impact. This study investigates the potential use of a residential grid-connected photovoltaic system in the Klang Valley of Malaysia. A 1-4 kW system would be capable of producing a RM 4,542.00 net profit per year, generating a total cash benefit of RM 95,382.00 in its 21 year project lifespan. Moreover, the system would significantly reduce greenhouse gas emissions (40,604 kg of carbon dioxide, 258 kg of sulfur dioxide, 120 kg of nitrous oxide, and 23 kg of carbon monoxide) throughout its 21 year project lifespan. The results of this study can be used to formulate effective renewable-energy alternatives in Malaysia and elsewhere. (c) 2014 American Institute of Chemical Engineers Environ Prog, 34: 866-880, 2015